Heavy/light chain assay in the monitoring of multiple myeloma - Ting, Huong Yew; Sthaneshwar, Pavai; Bee, Ping Chong; Shanmugam, Hemalatha; Lim, Merrell (Elsevier, 2019)
Serum protein (SPE) and immunofixation electrophoresis (IFE) have been extensively validated for the routine use of identifying, characterising and quantifying monoclonal proteins. However, accurate quantitation of IgA monoclonal proteins can be difficult when they migrate in to the β fraction, due to co-migration with transferrin and complement components. The heavy/light chain (HLC) immunoassay is an additional tool for measuring intact immunoglobulin monoclonal proteins. Therefore, we aimed to examine the clinical utility of the HLC assay for the disease monitoring of IgG and IgA multiple myeloma (MM) patients. A total of 177 samples from 30 MM patients (21 IgG and 9 IgA) were analysed retrospectively with median number of six follow up samples per patient (range 3–13). Serum free light chains (sFLC) and HLC were quantified using Freelite and Hevylite immunoassays. Details of M-protein concentration, β-globulin levels, total immunoglobulin levels and disease treatment response were obtained from the laboratory and patient information system. Passing–Bablok regression analysis was performed to compare (i) M-protein quantification with involved HLC (iHLC) and (ii) total immunoglobulin with summated HLC pairs for each immunoglobulin type (e.g., IgGκ+IgGλ). For 127 IgG MM samples, IgG iHLC levels showed a good correlation with SPE quantification (iHLC y=0.96x+4.9; r=0.917) and summated HLC showed a good correlation with total IgG concentration (summated HLC y=0.94x+5.74; r=0.91). In total, 95/127 (75%) IgG MM follow-up samples had an abnormal HLC ratio and 122/127 (96%) had a positive SPE, probably due to the lower sensitivity of HLC assay in detecting clonality in patients with IgG MM. Consistent with this, one patient assigned a very good partial response by International Myeloma Working Group criteria would be assigned a complete response based on HLC measurements. For 50 IgA MM samples, 42/50 (84%) had an abnormal HLC ratio. Conversely, 50/50 (100%) of M-proteins showed β fraction migration and were difficult to accurately quantify by SPE. Therefore, M-protein concentration and iHLC did not correlate as well in IgA MM (y=1.9x–8.4; r=0.8) compared to IgG MM. However, there was good correlation between total IgA and summated IgA HLC (IgAκ+IgAλ y=1.35x–0.33; r=0.95). Of the 8/50 (16%) IgA samples with a normal HLC ratio, 6/8 (75%) were consistent with the disease status being in complete remission. Interestingly, in one IgA MM patient, SPE and IFE were negative, but the serum FLC ratio and involved FLC were highly abnormal, consistent with the presence of light chain escape. Our data suggest HLC measurements could add value to the current disease monitoring of MM patients. In IgG MM patients, the M-protein level correlated well with HLC values. The HLC assay complements the serum FLC assay and is especially useful for monitoring of IgA MM patients who display M-proteins migrating in the β region on SPE. © 2019 Royal College of Pathologists of Australasia